Final Wishes: End-of-Life Decisions - Carolyn S. Wilken (EDIS, 2006)
FCS2262, a 3-page fact sheet by Carolyn Wilken, is the fifth in a series on caregiving and aging. Do you know what your loved ones would want if they were unable to make health decisions for themselves anymore? Do your loved ones know what your wishes would be? This publication refers readers to an inexpensive set of materials called Five Wishes that can help families lay out their preferences for end-of-life decisions ahead of time. When completed, the documents are legal in 38 states. This publication also includes a list of questions to help readers begin thinking about these issues. Published by the UF Department of Family, Youth and Community Sciences, November 2006.